Saúde do trabalhador da saúde : com a palavra a Secretaria Municipal de Saúde - Brotto, Tullio Cezar de Aguiar (2012)
Working has been asserted as a place of desirable meaningness, source of self-evaluation, self-perception and subjects production. It can be seen therefore, as a stage for subjective expressions and political conflicts. Thus, the relationship built between the worker and his duties supersedes the mere execution of coordinated tasks aiming at a product, decisively influencing on this workers health, having the organization of the work process an essential role in this process. However, what the scientific literature states to the health sector is the presence still remarkable of work management patterns focused on the production process and treats the workers as resources to be preserved in order to sustain such production. Manufacturing inspired patterns. Nevertheless, the literature also points to the significant sickening of health sector workers. For this reason, policies and guidelines have been conceived in both national and international levels aiming at this group, which led the World Health Organization (WHO) to elect the period of 2006-2016 as the decade of the work and health workers appreciation. Thus, this essay investigated Vitória s Municipal Health Department s understanding of the health care workers health. Intended to understand what this government agency conception of the causes of the sickening amongst health workers was and their coping proposals. We used the Thematic Content Analysis methodology (TCA) to analyze management reports and the Collective Subject Discourse methodology (CSD) to analyze the interviews. We interviewed 10 (ten) managers involved in the discussion of the Health Workers Health (HWH) issue. It was observed that this is not a consensus to the Department, however, it suggests a high rate of sickening among health workers. As for the causes of this sickening process there was a preponderance of workers characteristics attributed responses. The Department also claimed not to have a specific policy aiming at the decrease of this sickening process, although there are indirect policies such as the effective contracts and the improvement of infrastructural work conditions. However, asserted the increase of illnesses and work dissatisfaction rates in this same period. One of the causes seems to be the decreased of co-management. It was concluded that strategies seeking the decrease of the sickening process of health workers should not underestimate the co-management, once they will be confirming hegemonic management patterns that expropriate workers autonomy, reducing their chances of managing their work and obtaining pleasure from it.